RESPON PEMBERIAN ZAT PENGATUR TUMBUH (ZPT)BERBAHANAKTIF NAPHTHALENE ACETIC ACID (NAA)TERHADAPPERTUMBUHAN STEK TRUBUSAN DARI TUNGGUL SISAPENEBANGAN Eucalyptus pellita - Maimun Usria; M. Mardhiansyah '; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Coppicesof Eucalyptus pellita have the potential to produce seeds, so it takes a vegetative plant propagation by cuttings to meet the supply of seed planting. One of the factors that affect success rate of cuttings is the content of plant growth regulator (PGR) as Naphthalene Acetic Acid (NAA) from the category of auxin. This research aim to determine effect and exact concentration of PGR containing active NAA toward the growth of coppice cuttings. This research used a completely randomized design (CRD), which consists of 4 treatment (P0 = Without PGR containing active NAA; P1 = PGR containing active NAA 25%; P2 = PGR containing active NAA 50%; P3 = PGR containing activeNAA 75%), with 3 replications and 10 cuttings each. The results were analyzed using variance and if it is distinctively different it will be continued with Duncan New's Multiple Range Test on the level of 5%. The results showed that giving plant growth regulator containing active NAA not significantly yet toward the growth of Eucalyptus pellita coppice cuttings. Giving PGR containing active NAA at a concetration of 25 % and 75 % concentration inclined to be better toward thegrowth of Eucalyptus pellitacoppice cuttings. Keywords: Cuttings, Coppice, Eucalyptus pellita, Naphthalene Acetic Acid(NAA)